Common Coupled Fixed Point Theorems on C⋆-Algebra-Valued Partial Metric Spaces. (24th January 2022) - Mani, Gunaseelan; Gnanaprakasam, Arul Joseph; Khumalo, Precious B.; Gaba, Yaé U.
Abstract : In this paper, we prove common coupled fixed point theorems on complete C ⋆ -algebra-valued partial metric spaces. An example and application to support our result are presented.